Effects of precursor topology on polymer networks simulated with molecular dynamics. (5th May 2017) - Zhang, Shimiao; Xi, Li
Abstract: Molecular modeling of crosslinked polymers often follows arbitrary pathways for network generation, with different precursor topology from experimental systems. We use coarse-grained molecular simulation to study the effects of precursor choice on the predicted network structure and properties. Three sets of precursors with different molecular architectures are designed such that they would form identical networks at the limit of perfect conversion. Little difference is observed between the resulting networks in typical properties including the radial distribution function, macroscopic statistics of network connectivity, and glass transition behaviors. However, the stress-strain relationship in tensile deformation clearly depends on the formation pathway when compared at the same crosslinking density. The elastic modulus of the network is found to correlate strongly with the number of elastic strands in the network, except at the highly-crosslinked limit where substantial discrepancy is observed between networks from different precursors. Although these final networks contain a similar average density of structural defects, the choice of precursor has significant impact on their spatial distribution, leading to the precursor dependence of their mechanical properties. Uniform defect distribution and fast defect elimination can be achieved by designing precursor units with a proper stoichiometric ratio of different monomers. Graphical abstract: Highlights: Precursor topology affects polymer networks generated by molecular dynamics. At the same crosslinking density, spatial distribution of network defects may differ. Spatial clustering of defects results in stiffer networks in tensile tests. Precursors with the stoichiometric ratio of monomers form more uniform networks. Precursor topology also affects the speed of network formation.